2019
DOI: 10.3390/ijms20174115
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in Silico Characterization of GT Factors Involved in Phytohormone and Abiotic Stresses Responses in Brachypodium distachyon

Abstract: GT factors play critical roles in plant growth and development and in response to various environmental stimuli. Considering the new functions of GT factors on the regulation of plant stress tolerance and seeing as few studies on Brachypodium distachyon were available, we identified GT genes in B. distachyon, and the gene characterizations and phylogenies were systematically analyzed. Thirty-one members of BdGT genes were distributed on all five chromosomes with different densities. All the BdGTs could be divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Early research revealed that the GT factor family regulates morphogenetic processes and acts as a class of light regulators, which explains their roles in controlling light-responsive genes [ 45 ]. However, more recent studies have provided compelling evidence that the trihelix family also plays a significant role in plant growth and development and the responsiveness to environmental cues [ 27 , 46 ]. In this study, we identified 40 trihelix genes in the C. sinensis genome, distributed across chromosomes with varying densities.…”
Section: Discussionmentioning
confidence: 99%
“…Early research revealed that the GT factor family regulates morphogenetic processes and acts as a class of light regulators, which explains their roles in controlling light-responsive genes [ 45 ]. However, more recent studies have provided compelling evidence that the trihelix family also plays a significant role in plant growth and development and the responsiveness to environmental cues [ 27 , 46 ]. In this study, we identified 40 trihelix genes in the C. sinensis genome, distributed across chromosomes with varying densities.…”
Section: Discussionmentioning
confidence: 99%